2014
DOI: 10.1136/bmjopen-2014-005404
|View full text |Cite
|
Sign up to set email alerts
|

The first 1000 days of life: prenatal and postnatal risk factors for morbidity and growth in a birth cohort in southern India

Abstract: ObjectiveTo estimate the burden and assess prenatal and postnatal determinants of illnesses experienced by children residing in a semiurban slum, during the first 1000 days of life.DesignCommunity-based birth cohortSettingSouthern IndiaParticipantsFour hundred and ninety-seven children of 561 pregnant women recruited and followed for 2 years with surveillance and anthropometry.Main outcome measureIncidence rates of illness; rates of clinic visits and hospitalisations; factors associated with low birth weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 38 publications
1
44
0
19
Order By: Relevance
“…Although the maternal educational level is very commonly associated with stunting, the causal mechanism is not known; this variable may be a proxy for socioeconomic status or a determinant of the maternal-infant interaction, use of health services, or maternal diet. Finally, boys have shown higher rates of clinical illness in early life (6163), potentially because of differences in inflammatory and immune responses compared with girls, as has been suggested by sex differences in the immune response to vaccination (64) and infectious diseases (63). It has also been suggested that natural selection may favor maximizing reproductive fitness, thereby resulting in higher morbidity and mortality rates in male infants to compensate for greater male birth rates (65, 66).…”
Section: Discussionmentioning
confidence: 99%
“…Although the maternal educational level is very commonly associated with stunting, the causal mechanism is not known; this variable may be a proxy for socioeconomic status or a determinant of the maternal-infant interaction, use of health services, or maternal diet. Finally, boys have shown higher rates of clinical illness in early life (6163), potentially because of differences in inflammatory and immune responses compared with girls, as has been suggested by sex differences in the immune response to vaccination (64) and infectious diseases (63). It has also been suggested that natural selection may favor maximizing reproductive fitness, thereby resulting in higher morbidity and mortality rates in male infants to compensate for greater male birth rates (65, 66).…”
Section: Discussionmentioning
confidence: 99%
“…that investigated symptomatic and asymptomatic cryptosporidial infections in 497 children during the first 3 years of their life through biweekly followup visits. 35 Ethical approvals for both studies were obtained from the Institutional Review Boards of Christian Medical College, Vellore and Tufts University Health Sciences Campus, Boston. Written informed consent was provided by parents or legal guardians of all participating children, before enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…1618 The studies were approved by the Institutional Review Boards of the Christian Medical College, Vellore, India and Tufts University Health Sciences campus, Boston, USA. The data set includes 982 children who were followed weekly or twice-weekly from birth to 3 years of age.…”
Section: Methodsmentioning
confidence: 99%